2015
DOI: 10.1016/j.celrep.2015.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Human Severe Combined Immunodeficiency and Correction by CRISPR/Cas9-Enhanced Gene Targeting

Abstract: Mutations of the Janus family kinase JAK3 gene cause severe combined immunodeficiency (SCID). JAK3 deficiency in humans is characterized by the absence of circulating T cells and natural killer (NK) cells with normal numbers of poorly functioning B cells (T(-)B(+)NK(-)). Using SCID patient-specific induced pluripotent stem cells (iPSCs) and a T cell in vitro differentiation system, we demonstrate a complete block in early T cell development of JAK3-deficient cells. Correction of the JAK3 mutation by CRISPR/Cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(64 citation statements)
references
References 56 publications
0
61
0
3
Order By: Relevance
“…In a separate study, Chang and colleagues successfully correct a JAK3 mutation in SCID-iPSCs using CRISPR technology. The corrected cells also regained the differentiation potentials to T cell progenitors (Chang et al 2015). Although functional outcomes were not examined in a third study with iPSCs derived from an ADA-SCID patient, Howden and colleagues combined the reprogramming and genome-editing processes together and successfully generated ADA gene-corrected patient-iPSCs in a shortened time frame (Howden et al 2015).…”
Section: Corrections Of Disease-associated Genetic Mutations In Patiementioning
confidence: 93%
See 1 more Smart Citation
“…In a separate study, Chang and colleagues successfully correct a JAK3 mutation in SCID-iPSCs using CRISPR technology. The corrected cells also regained the differentiation potentials to T cell progenitors (Chang et al 2015). Although functional outcomes were not examined in a third study with iPSCs derived from an ADA-SCID patient, Howden and colleagues combined the reprogramming and genome-editing processes together and successfully generated ADA gene-corrected patient-iPSCs in a shortened time frame (Howden et al 2015).…”
Section: Corrections Of Disease-associated Genetic Mutations In Patiementioning
confidence: 93%
“…Similar to sickle cell disease and thalassemias, SCID patients can benefit from genetically corrected iPSCs that potentially may provide alternative sources for transplantation. Recently, three studies have been reported that iPSCs derived from different forms of SCID have been gene-corrected with TALEN and CRISPR endonucleases (Chang et al 2015; Howden et al 2015; Menon et al 2015). Menon and colleagues used the TALEN technology to correct a splice-site mutation in the interleukin-2 receptor gamma chain (IL-2Rγ) gene, which is required for the differentiation and maturation of the majority of lymphocytes.…”
Section: Corrections Of Disease-associated Genetic Mutations In Patiementioning
confidence: 99%
“…Similar to the other gene editing technologies discussed here, CRISPR/Cas9 methods have been extensively applied in hiPSC to develop models of immunodeficiency and blood diseases including β-Thalssemia [167,168], hemophilia [169], ICF syndrome [170], sickle cell disease [171], and severe combined immunodeficiency [172]. More recently, CRISPR/Cas9 techniques have been combined with advanced bioengineering culture techniques to create more accurate in vitro disease models [173,174].…”
Section: Applications Of Gene Editing Technologies With Hipscsmentioning
confidence: 99%
“…Additionally, the use of iPSCs bypasses the issue of HLA-matching as they are patient-derived, and also allows for the generation of T cells from patients who are completely T cell deficient, since any somatic cell can be corrected and reprogrammed, although it should be noted that T cell generation from non-T cell sourced iPSCs is far less efficient than from T cell-derived iPSCs. Still, this enables the study of T cells in their normal and aberrant forms, elucidating novel disease mechanisms [43] and validating gene-correction therapies in JAK3- and IL-2Rγ-deficient iPSCs by gene-specific correction using CRISPR or TALEN-mediated approaches [41, 42]. In another study involving IL-2R-γ deficiency, CD34 + HSPCs of patients, for which there was no suitable HLA identical donor, received γ-retroviral treatment [48].…”
Section: Generating T Cells From Various Cell Sourcesmentioning
confidence: 99%